Optimalisasi Potensi Jagung Lokal melalui Pelatihan Pembuatan Wajik Sehat di Desa Billa Kabupaten Timor Tengah Selatan: Optimizing Local Corn Potential through Healthy Wajik Production Training in Billa Village Timor Tengah Selatan Regency - Latumakulita, Gertreda; Pote, Lodowik Landi; Kadebu, Juliano M. P. Umbu Jima; Tukan, Amandha Victoria Dwiputri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Billa Village, located in the South Central Timor Regency, is known as a major corn-producing area with abundant harvests. However, this agricultural potential has yet to be fully harnessed by the local community, particularly in transforming raw produce into nutritious and economically valuable products. The situation is further complicated by limited access to electricity and a high prevalence of malnutrition, especially among homemakers. In response to these challenges, this community service initiative was designed to empower residents through a participatory training program focused on producing healthy corn-based snacks—specifically wajik jagung—using locally sourced ingredients. The training involved close coordination with local partners, preparation of tools and materials, hands-on technical sessions, and evaluation of outcomes. Throughout the process, participants demonstrated improved understanding and skills in processing corn into nutritious food, and began taking initial steps toward simple product marketing strategies.